Settlement pattern in regional planning: (A study of the Central Region) - Anipa, Seth Emanuel Komla (2011)
A Thesis Presented to the Faculty of Architecture Of University of Science and Technology In partial fulfillment of the requirements for the degree of Master of Science in Regional Planning, 1967